2019
DOI: 10.1111/jcmm.14711
|View full text |Cite
|
Sign up to set email alerts
|

A novel single‐chain enzyme complex with chain reaction properties rapidly producing thromboxane A2 and exhibiting powerful anti‐bleeding functions

Abstract: Uncontrollable bleeding is still a worldwide killer. In this study, we aimed to investigate a novel approach to exhibit effective haemostatic properties, which could possibly save lives in various bleeding emergencies. According to the structure‐based enzymatic design, we have engineered a novel single‐chain hybrid enzyme complex (SCHEC), COX‐1‐10aa‐TXAS. We linked the C‐terminus of cyclooxygenase‐1 (COX‐1) to the N‐terminus of the thromboxane A2 (TXA2) synthase (TXAS), through a 10‐amino acid residue linker. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In fact, at low concentrations (2 μg/mL), arachidonate can induce platelet activation and phosphatidylserine exposure and promote a procoagulant state [ 92 ]. In addition, cyclooxygenase-1 can convert arachidonate into thromboxane A2 (TxA2) [ 93 , 94 ], thus amplifying the vesicular arachidonate effects [ [95] , [96] , [97] ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at low concentrations (2 μg/mL), arachidonate can induce platelet activation and phosphatidylserine exposure and promote a procoagulant state [ 92 ]. In addition, cyclooxygenase-1 can convert arachidonate into thromboxane A2 (TxA2) [ 93 , 94 ], thus amplifying the vesicular arachidonate effects [ [95] , [96] , [97] ].…”
Section: Discussionmentioning
confidence: 99%
“…TXA 2 and PGI 2 are vasoactive substances, which are endogenous metabolites closely related to the formation mechanism of AUB and regulate hemodynamics in the endothelium. TXA 2 has a strong vasoconstrictive effect and promotes platelet aggregation and release [ 17 ], while PGI 2 is synthesized by the endothelial cells of blood vessels and has vasodilatory and platelet-inhibiting effects. Under normal conditions, TXA 2 and PGI 2 are in a dynamic balance, jointly regulating vasoconstriction and dilation and participating in the regulation of blood clotting [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experimental studies have shown that total flavonoids of Limonium bicolor, Sedum auriculatum, and purple pearl can significantly reduce bleeding and clotting time in mice. The mechanism of action may be through regulating the imbalance of TXA2 and PGI2, enhancing the contraction of small blood vessels in the endometrium to achieve hemostasis [ 58 ]. Therefore, we speculate that isorhamnetin, catechins and other flavonoids in YZG also regulate the expression of the PTGS gene to strengthen endometrial vasoconstriction and platelet aggregation, thereby achieving a hemostatic effect.…”
Section: Discussionmentioning
confidence: 99%